"It's Not Being Racist, but ... ": A Youth Gang and the Creation of Belonging Based on "Othering". Issue 2 (1st December 2019) - Gormally, Sinead
Abstract : This article explores the tacit endorsement of male youth gang members engaging in "race"-based conflict to gain localized levels of power. It examines the importance of belonging to an "in-group" for these young people via their connectedness to the broader residents, through cultural essentialism toward a Roma "out-group." The young, male gang members, drawing on what they perceive to be their role, adopt physical and symbolic strategies to assert their control over their space and to concretize their sense of belonging with the wider community in-group. The article considers how a labeled and excluded group of male youth gang members from wider social structures find connection, commonality, and belonging in hardening their self-image through an othering process against those deemed inferior to them.